2020
DOI: 10.1055/s-0040-1714427
|View full text |Cite
|
Sign up to set email alerts
|

Perforator Mapping Practice for Deep Inferior Epigastric Artery Perforator Flap Reconstructions: A Survey of the Benelux Region

Abstract: Background Numerous new and novel imaging techniques for preoperative perforator selection in deep inferior epigastric artery perforator (DIEP) flap planning have been introduced. To what extent, these have been adopted into or replaced routine practice has hitherto remained unknown. The purpose of this study was to identify the currently preferred technique by reconstructive surgeons, the criteria that they regard as most relevant and what impact these have on the preoperative decision-making. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Ninety-one percent of surgeons in that study opted for CTA as their imaging modality of choice with the additional 6% preferring MRA. 14 Our study showed that CTA/MRA detected the perforators on which the DIEP was ultimately based with a sensitivity of 70.1%. This value is somewhat lower than what is currently described in the cadaveric and small studies populating the literature.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Ninety-one percent of surgeons in that study opted for CTA as their imaging modality of choice with the additional 6% preferring MRA. 14 Our study showed that CTA/MRA detected the perforators on which the DIEP was ultimately based with a sensitivity of 70.1%. This value is somewhat lower than what is currently described in the cadaveric and small studies populating the literature.…”
Section: Discussionmentioning
confidence: 54%
“…Ninety-one percent of surgeons in that study opted for CTA as their imaging modality of choice with the additional 6% preferring MRA. 14…”
Section: Discussionmentioning
confidence: 99%
“…39 While preoperative imaging allows for vascular mapping and better understanding of perforator anatomy, we do not recommend it routinely. [40][41][42] Instead, it adds an additional procedure for the patient and an inconvenience factor especially since a large portion of breast reconstructions are done in an ambulatory surgery center, in which case the imaging would have to be done elsewhere first. Furthermore, increased BMI also limits CTA for presurgical planning due to decreased visualization of perforators with increased body weight.…”
Section: Discussionmentioning
confidence: 99%
“…3 4 5 In fact, a recent survey of practicing microsurgeons in Belgium, the Netherlands, and Luxembourg showed that 97% preferred CTA for routine postoperative imaging despite the existence of nonradiation requiring alternatives. 15…”
Section: Computed Tomography Angiographymentioning
confidence: 99%